The evolution of comparative advantage: Measurement and implications - Andrei A. Levchenko; Jing Zhang (Federal Reserve Bank of Chicago, 2014)
We estimate productivities at the sector level for 72 countries and 5 decades, and examine how they evolve over time in both developed and developing countries. In both country groups, comparative advantage has become weaker: productivity grew systematically faster in sectors that were initially at greater comparative disadvantage. These changes have had a significant impact on trade volumes and patterns, and a non-negligible welfare impact. In the counterfactual scenario in which each country's comparative advantage remained the same as in the 1960s, and technology in all sectors grew at the same country-specific average rate, trade volumes would be higher, cross-country export patterns more dissimilar, and intra-industry trade lower than in the data. In this counterfactual scenario, welfare is also 1.6% higher for the median country compared to the baseline. The welfare impact varies greatly across countries, ranging from ..1.1% to +4.3% among OECD countries, and from ..4.6% to +41.9% among non-OECD countries.
Keywords: F11; F43; O33; O47; 330; technological change; sectoral TFP; Ricardian models of trade; welfare